2021
DOI: 10.1097/md.0000000000025016
|View full text |Cite
|
Sign up to set email alerts
|

Suitability of h- and x-indices for evaluating authors’ individual research achievements in a given short period of years

Abstract: Background: The h-index of a researcher refers to the maximum number h of his/her publications that has at least h citations via the concept of the square area. The x-index is determined by the maximum area of a rectangle under the curve to interpret authors’ individual research achievements (IRAs). However, the properties of both metrics have not been compared and discussed before. This study aimed to investigate whether both metrics of h- and x-index are suitable for evaluating IRAs in a short p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…Several bibliographical studies used visualization to explore only 1 aspect of research (e.g., Citation analysis; Theme exploration; Topic analysis; Reference citations; Research; Research achievement; Author collaboration, and; Trend and hot spot in terms and articles [ 22 , 23 , 38 , 45 , 57 , 58 ] ). It was not found that such research was conducted to condense information in a concise 4-quadrant radar plot (e.g., Figs.…”
Section: Discussionmentioning
confidence: 99%
“…Several bibliographical studies used visualization to explore only 1 aspect of research (e.g., Citation analysis; Theme exploration; Topic analysis; Reference citations; Research; Research achievement; Author collaboration, and; Trend and hot spot in terms and articles [ 22 , 23 , 38 , 45 , 57 , 58 ] ). It was not found that such research was conducted to condense information in a concise 4-quadrant radar plot (e.g., Figs.…”
Section: Discussionmentioning
confidence: 99%
“…Lotka’s law was applied to identify the most productive co-authors [ 73 ]. The Hirsch index (h-index) was used to identify the most prominent co-authors, with the most productive being those with the highest number of citations among the analysed papers [ 74 , 75 ]. The most relevant contributions were considered to be those with h or the highest number of citations, based on the h-index [ 75 , 76 ].…”
Section: Methodsmentioning
confidence: 99%
“…The bootstrapping method [15,31,32] was performed to verify the difference in mean citations for each theme between the groups. A total of 1000 medians were retrieved from random samples of 100 repetitions of median values for each theme in each group.…”
Section: Methodsmentioning
confidence: 99%